(3EOGQI GdGSJKeGQ hGdeMGaX GdGSJKeGQjI (B/s - (3GdOhQj, eDjO YHO GdQMeGfs ((3YeGf(B: s (3GKQGA(B, s, 2010)
(3eaghe GdGSJKeGQ h CgOGag , GdGShGb GdeGdjI h GdCOhGJ GdGSJKeGQjI , GdYGFO h GdeNGWQI , Jbjje GdSfOGJ h Jbjje GdCSge , TQcGJ GdGSJKeGQ , GdJfhjY h eNGWQ GdeMaXI , fehL JSYjQ GdCUhd GdQCSeGdjI , fXQjI JSYjQ GdeQGLMI , Jbjje COGA GdeMaXI h CNjQG GdeTJbGJ GdeGdjIs
Keywords: (3GdESJKeGQs; (3GdESJKeGQ `` EOGQIs; (3GdCShGb GdeGdjIs